Observation of successful treatment of the patient with intraventricular hemorrhage - Berezyuk, M. V.; Tsimeyko, O. A.; Moroz, V. V. (Ukrainian Neurosurgical Journal, 2008)
The new method of intraventricular hemorrhages treatment is described. The observation of patient’s with a primary hemorrhage treatment is given, the technique of local fibrinolysis is considered.